Pengaruh intervensi pangan lokal dan konseling gizi terhadap stunting pada balita - Widya Lestari Nurpratama; Nur Fauzia Asmi; Anom Dwi Prakoso (Jurnal SAGO Gizi dan Kesehatan, 2024)
Background: Handling of stunting can be done through comprehensive intervention and not only done with one intervention method, namely by providing local food according to the contents of my plate and nutritional education for mothers of toddlers through individual counseling methods.Objectives: The purpose of this study was to analyze the differences in Body Weight, Height, and maternal knowledge before and after local food intervention and nutritional counseling were carried out on stunted toddlers in Bekasi Regency.Method: Experimental research method, pre-experimental research design with one group pretest-posttest design model, conducted in Pasir Gombong Village, North Cikarang District, Bekasi. The research was conducted from August - September 2024. The subjects of the study were 15 stunted toddlers taken based on purposive sampling techniques according to inclusion and exclusion criteria and data processing using the Wilcoxon test. The interventions provided were nutritional counseling in two meetings, and feeding for 14 days. The data collected in the form of maternal nutritional knowledge and toddler characteristics were conducted through questionnaire interviews. Weight data was measured using a digital scale and toddler height was measured using a stature meter.Results: The average weight increased after the intervention by 0.1 kg, but was not significantly different (p = 0.148). The average height increased after the intervention by 0.2 cm and was significantly different (p = 0.027). Then the mother's knowledge increased by 7.7 points and was significantly different (p = 0.011).Conclusion: There are differences in weight, height, and knowledge of mothers of toddlers before and after local food intervention and nutrition education with the nutrition counseling method for stunted toddlers in Bekasi Regency.